Mycoplasma detection by triplex real-time PCR in bronchoalveolar lavage fluid from bovine respiratory disease complex cases - Cornelissen, Jan B. W. J. (BMC Vet Res, 2017)
BACKGROUND: In this study we evaluated the RespoCheck Mycoplasma triplex real-time PCR for the detection in bronchoalveolar lavage fluid (BALF) of Mycoplasma (M.) dispar, M. bovis and M. bovirhinis, all three associated with bovine respiratory disease (BRD). Primers and probes of the RespoCheck Mycoplasma triplex real-time PCR are based on the V3/V4 region of the 16S rRNA gene of the three Mycoplasma species. RESULTS: The analytical sensitivity of the RespoCheck triplex real-time PCR was, as determined by spiking experiments of the Mycoplasma strains in Phosphate Buffered Saline, 300 colony forming units (cfu)/mL for M. dispar, and 30 cfu/mL for M. bovis or M. bovirhinis. The analytical sensitivity of the RespoCheck Mycoplasma triplex real-time PCRwas, as determined on purified DNA, 10 fg DNA per assay for M. dispar and 100 fg fo rM. bovis and M. bovirhinis. The analytical specificity of the RespoCheck Mycoplasma triplex real-time PCR was, as determined by testing Mycoplasmas strains (n = 17) and other bacterial strains (n = 107), 100, 98.2 and 99.1% for M. bovis, M. dispar and M. bovirhinis respectively. The RespoCheck Mycoplasma triplex real-time PCR was compared with the PCR/DGGE analysis for M. bovis, M. dispar and M. bovirhinis respectively by testing 44 BALF samples from calves. CONCLUSION: In conclusion, the RespoCheck PCR assay can be a valuable tool for timely and accurate detection of three Mycoplasma species associated with in bovine respiratory disease.